The Influence of Regional Revenue, Balancing Funds, Special Autonomic Funds, and Economic Growth on Capital Expenditures Allocation - Jumiati, Eva; Indriani, Mirna; Darwanis, Darwanis (Universitas Syiah Kuala, 2019)
Objective This study aims to examine the effect of Regional Revenue, Balancing Funds, Special Autonomy Funds, and Economic Growth on the Allocation of Capital Expenditures in Regencies / Cities in Aceh for the period 2013-2017.Design/methodology This type of research is quantitative, the population of this study is all districts/cities in Aceh in 2013-2017, amounting to 23 local governments consisting of 18 district governments and 5 city governments. The unit of analysis of this research is the Realization Report of the Revenue and Expenditure Budget (LRA-APBK) in Aceh for the 2013-2017 Period which has been audited by the Financial Supervisory Agency (BPK) and Gross Regional Domestic Product (PDRB) data.Results The results of the study show that both jointly and separately, regional own-source revenues, balancing funds, special autonomy funds, and economic growth have an effect on the allocation of capital expenditures in districts/cities in Aceh for the period 2013-2017.Originality/Value Discussion related to the influence of special autonomy funds on capital expenditure is limited research, so it is deemed necessary to do as additional insight and reference of research results.